(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the syntactic structure of Nazar Eshonqul’s prose, a prominent figure in modern Uzbek literature. Through a detailed linguistic and stylistic analysis of selected works, the study examines how N.Eshonqul utilizes sentence construction, syntactic variety, connectors, and stylistic devices such as parallelism, repetition, inversion, and ellipsis to shape narrative rhythm and express psychological depth. Drawing from Uzbek oral traditions and modernist influences, N.Eshonqul’s prose demonstrates a unique blend of simplicity and complexity. His syntax is not merely grammatical but functions as a powerful literary tool that enhances thematic expression and reader engagement. The study highlights how N.Eshonqul’s manipulation of syntactic elements contributes to the philosophical and emotional resonance of his storytelling, marking his distinctive place in Uzbek literary prose.